IMPACT OF INFORMATION AND COMMUNICATION TECHNOLOGY ON BANK PERFORMANCE: A STUDY OF SELECTED COMMERCIAL BANKS IN NIGERIA (2001 – 2011) - Abubakar Muhammad; Nasir Mukhtar Gatawa; Haruna Sani Birnin Kebbi (European Scientific Journal, ESJ, 2013)
This study assessed the Impact of Information and Communication Technology on the Nigerian banking industry using eleven selected Commercial Banks in Nigeria. The study used bank annual data over the period 2001 to 2011. This study applied Fixed and Random Effects Models in its analysis. The results from the Hausman test revealed that Random Effects Model was appropriate. The findings of the study indicated that the use of ICT in the banking industry in Nigeria increases return on equity. It has also been found an inverse relationship between additional sustained investment in ICT and efficiency which the study recommends among other thing shifting more emphasis on policies that will boost efficient/proper utilization of ICT equipment rather than additional investments.